A Meta-Analytic Study of the Neural Systems for Auditory Processing of Lexical Tones - Kwok, Veronica P. Y.; Dan, Guo; Yakpo, Kofi; Matthews, Stephen; Fox, Peter T.; Li, Ping; Tan, Li-Hai (Frontiers in Human Neuroscience, 2017)
The neural systems of lexical tone processing have been studied for many years. However, previous findings have been mixed with regard to the hemispheric specialization for the perception of linguistic pitch patterns in native speakers of tonal language. In this study, we performed two activation likelihood estimation (ALE) meta-analyses, one on neuroimaging studies of auditory processing of lexical tones in tonal languages (17 studies), and the other on auditory processing of lexical information in non-tonal languages as a control analysis for comparison (15 studies). The lexical tone ALE analysis showed significant brain activations in bilateral inferior prefrontal regions, bilateral superior temporal regions and the right caudate. While the control ALE analysis showed significant cortical activity in the left inferior frontal gyrus and left temporo-parietal regions. However, we failed to obtain significant differences from the contrast analysis between two auditory conditions, which might be caused by the limited number of studies available for comparison. Although the current study lack evidence to argue for a lexical tone specific activation pattern, our results provide clues and directions for future investigations on this topic, more and more sophisticated methods are needed to explore this question in more depth as well.